Depression, Anxiety and Stress Scores Inmale and Female Students (International Journal of Physiology, 2021)
Psychological parameters play a key role in the daily life of young adults.It was reported that there wasa high incidence of suicidal rate in these age groups when compared with others. The present study wasundertaken to observe the selected psychological parameters that are depression, anxiety, and stress in youngadults. A total of 50 (males =25, females =25) young adults studying undergraduate allied health coursesboth males and females were part of the study after obtaining the written informed consent. The followingcriterion was used to recruit the participants. Depression, anxiety, and stress levels were assessed using theDASS-42 questionnaire. Depression scores were significantly higher in females when compared with males.Anxiety and stress scores were not significantly different among males and females. Females were in severedepression where males were moderate. Anxiety scores of males and females were mild. Stress scores ofmales and females were severe. The study results support earlier studies and emphasize the need to assesspsychological parameters in young adults. The study also recommends detailed studies in this area.